The Bacillus velezensis CYS06 Strain Exhibits Promising Applications in Fighting Grass Carp Bacterial Diseases - Lijuan Liu; Dongdong Jiang; Yan Ren; Cunbin Shi; Yajun Wang; Jiyuan Yin; Qing Wang; Defeng Zhang (Fishes, 2023)
Aeromonas septicemia and columnaris disease are major bacterial diseases in grass carp; however, the drugs currently used to control these diseases pose environmental and health risks. This study aimed to screen for a probiotic Bacillus strain with antagonistic activity to prevent and control bacterial diseases in grass carp and to evaluate the antimicrobial activities, biosafety, and biocontrol effects of this strain. A Bacillus strain with antagonistic activity against Aeromonas hydrophila, obtained from grass carp intestines, was screened, and the isolate CYS06 was identified by analyzing the 16S rRNA and gyrA gene sequences. The antimicrobial spectrum of the strain CYS06 was determined, and the activities of amylase, cellulase, protease, and lipase of the strain CYS06 were determined. The whole genome of the strain CYS06 was sequenced using the nanopore sequencing technology platform, followed by the analysis of the antagonistic substance synthesis gene clusters and CAZy enzyme gene families. The biosafety of the strain CYS06 was evaluated via intraperitoneal injection into healthy grass carp. After the strain CYS06 was fed to the grass carp, its biological control effect on this fish was evaluated through artificial infection experiments. The strain CYS06 was identified as Bacillus velezensis, based on molecular identification, which shows broad antimicrobial activity against various fish pathogens. The strain CYS06 secretes amylase, cellulase, protease, and lipase. The genome size of the strain CYS06 is 3,914,159 bp, and it contains eight antagonistic substance synthesis gene clusters and many CAZy enzymes. The strain CYS06 exhibits high biological safety for grass carp, based on the challenge test. Feeding grass carp with the strain CYS06 for 4 weeks significantly enhanced the resistance of the fish to A. hydrophila. Strain CYS06 could inhibit the growth of Flavobacterium columnare under co-culture and reduce the amount of F. columnare adherence on the gills of grass carp, indicating that CYS06 has good potential for the prevention and control of columnaris disease. In conclusion, we isolated an antagonistic probiotic strain, CYS06, which exhibits a biological control effect on septicemia and columnaris disease caused by Aeromonas spp. and F. columnare in grass carp, respectively. This strain contains many antagonistic substance synthesis-related gene clusters and holds the potential to degrade various types of carbohydrates. As a biological control agent, the strain CYS06 exhibits significant potential for the prevention and control of bacterial diseases in grass carp.